Small scale parallel manipulator kinematics for flexible snake robot application - Khan, Md. Raisuddin; Billah, Md. Masum; Watenabe, Mitsuru; Shafie, Amir Akramin (American Society of Science and Engineering, 2014)
A small-scale parallel manipulator is designed in this paper. The kinematic analysis of the manipulator is also elucidated for the development of multilinked snake robot. A compliant central colum is used to connect two parallel platforms of Incompletely Restrained Positioning Mechanism (IRPM). The compliant column allows the configuration to achieve 3 DOFs with 3 tendons of active materials connected between the upper and loer platform of the mechanism. In particular, this investigation focuses on the angular deflection of the upper platform with respect to the lower platform. The application here is aimed at developing an active linkable module that can be connected to one another so as to form a “snake robot” of sorts. For an arbitrary angular displacement of the platforms, the corresponding length of each tendon can be determined through inverse kinematics. From the experimental result, the extreme bending of the central column plane of 30° angular displacement with the of the horizontal axis.